Audit committee, board of director characteristics, and earnings management - Klein, April (Journal of Accounting and Economics, 2002)
This study examines whether audit committee and board characteristics are related to earnings management by the firm. A negative relation is found between audit committee independence and abnormal accruals. A negative relation is also found between board independence and abnormal accruals. Reductions in board or audit committee independence are accompanied by large increases in abnormal accruals. The most pronounced effects occur when either the board or the audit committee is comprised of a minority of outside directors. These results suggest that boards structured to be more independent of the CEO are more effective in monitoring the corporate financial accounting process.